Selective Radiofrequency Stimulation of the Dorsal Root Ganglion (DRG) as a Method for Predicting Targets for Neuromodulation in Patients With Post Amputation Pain: A Case Series. Issue 7 (23rd March 2017) - Hunter, Corey W.; Yang, Ajax; Davis, Tim
Abstract : Objective: While spinal cord stimulation (SCS) has established itself as an accepted and validated treatment for neuropathic pain, there are a number of conditions where it has experienced less, long‐term success: post amputee pain (PAP) being one of them. Dorsal root ganglion (DRG) stimulation has shown great promise, particularly in conditions where traditional SCS has fallen short. One major difference between DRG stimulation and traditional SCS is the ability to provide focal stimulation over targeted areas. While this may be a contributing factor to its superiority, it can also be a limitation insofar stimulating the wrong DRG(s) can lead to failure. This is particularly relevant in conditions like PAP where neuroplastic maladaptation occurs causing the pain to deviate from expected patterns, thus creating uncertainty and variability in predicting targets for stimulation. We propose selective radiofrequency (RF) stimulation of the DRG as a method for preoperatively predicting targets for neuromodulation in patients with PAP. Methods: We present four patients with PAP of the lower extremities. RF stimulation was used to selectively stimulate individual DRG's, creating areas of paresthesias to see which most closely correlated/overlapped with the painful area(s). RF stimulation to the DRG's that resulted in the desirable paresthesia coverage in the residual or the missing limb(s) was recorded as "positive." Trial DRG leads were placed based on the positive RF stimulation findings. Results: In each patient, stimulating one or more DRG(s) produced paresthesias patterns that were contradictory to know dermatomal patterns. Upon completion of a one‐week trial all four patients reported 60–90% pain relief, with coverage over the painful areas, and opted for permanent implant. Conclusions: Mapping the DRG via RF stimulation appears to provide improved accuracy for determining lead placement in the setting of PAP where pain patterns are known to deviate from conventional dermatomal mapping.